Phase diagram of polymerizing nitrogen – a theoretical prediction - Yakub, L.N. (Хабаршы. Физика сериясы, 2015)
Polymerization of nitrogen molecules in both solid and liquid phases, which was discovered in dynamic and static experiments, and predicted in ab initio simulations, stimulated discussion on a new configuration of phase diagram of nitrogen at high pressures. We consider the high-pressure phase diagram of solid nitrogen, which has long been discussed in theoretical studies, and only in the last decade began to investigate experimentally.